Efficient one-pot synthesis of 3, 7-disubstituted 1, 6-naphthyridin-2(1H)-ones through regioselective palladium-catalyzed cross-coupling and SNAr reactions. Issue 21 (27th May 2015) - Montoir, David; Tonnerre, Alain; Duflos, Muriel; Bazin, Marc-Antoine
Abstract: An efficient synthesis of original 3, 7-disubstituted 1, 6-naphthyridones via one-pot palladium-catalyzed cross-coupling and SN Ar reactions is reported. Buchwald–Hartwig amination was investigated to introduce a large variety of nitrogen-containing nucleophiles at position 3 of 1, 6-naphthyridones. Then, palladium-catalyzed C - and N -arylation or SN Ar reactions were employed to functionalize the position 7. This one-pot approach afforded highly functionalized 1, 6-naphthyridin-2(1 H )-ones in good yields. Graphical abstract: